2010
DOI: 10.1074/jbc.m109.061713
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Kinase Homology Domain Is Essential for the Activity of Photoreceptor Guanylate Cyclase 1

Abstract: Phototransduction is carried out by a signaling pathway that links photoactivation of visual pigments in retinal photoreceptor cells to a change in their membrane potential. Upon photoactivation, the second messenger of phototransduction, cyclic GMP, is rapidly degraded and must be replenished during the recovery phase of phototransduction by photoreceptor guanylate cyclases (GCs) GC1 (or GC-E) and GC2 (or GC-F) to maintain vision. Here, we present data that address the role of the GC kinase homology (KH) doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Recent studies by Bereta et al, have demonstrated phosphorylation at four serine residues within the kinase homology domain of guanylyl cyclase 1 (GC1) (also known as GC-E) from mouse retina using mass spectrometry (26). Interestingly, the four phosphorylation sites identified within the kinase homology domain of GC1 align with the highly phosphorylated region of the kinase homology domains of GC-A and GC-B.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Bereta et al, have demonstrated phosphorylation at four serine residues within the kinase homology domain of guanylyl cyclase 1 (GC1) (also known as GC-E) from mouse retina using mass spectrometry (26). Interestingly, the four phosphorylation sites identified within the kinase homology domain of GC1 align with the highly phosphorylated region of the kinase homology domains of GC-A and GC-B.…”
Section: Discussionmentioning
confidence: 99%
“…42 Purification of ABCA4 was performed by immunoprecipitation on ice under dim red light. ROS from 10 mouse retinas were solubilized with 1 mL of buffer containing 10 mM sodium phosphate (pH 7.6), 50 mM NaCl, 50 mM NaF, 10 mM EDTA, 30 mM DDM, 10% glycerol, 0.1 mM DTT, and 10 nM okadaic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Although the function of the KHD is unclear, it was shown to be essential for interaction with guanylate cyclase activating proteins (GCAPs) (Duda et al, 1996; Laura and Hurley, 1998). Further, it was shown that photoreceptor GC1 auto-phosphorylates serine residues of the 529-GSRSSLGARS motif (Bereta et al, 2010). The predominantly outer segment localization of GCct4 suggested the possibility that the KHD might contain targeting information.…”
Section: Resultsmentioning
confidence: 99%